Directions for improvement of mechanochemical processes of utilizing ore tailings - Vladimir I Golik; Valery B Kelekhsaev; Yuri A Majstrov; Aslan S Olisaev (RUDN Journal of Engineering Research, 2018)
Аbstract. The article is devoted to the problem of waste-free extraction of metals from the tailings of primary ore processing. It represents a generalized approach of development of a mechanochemical technology of metal extraction by leaching in disintegrator and includes a summary of existing views on the problem, an analysis of prospects of the technology and the real steps taken in this direction. In the article, the theory and practice of mechanochemical extraction of metals from ores is examined and the assessment of the existing state of subject matter is given. The essence of the problem is that for the expansion of applications of the recommended technology, it must be improved. The article includes an introduction, a purpose statement and the results of improvement on the level of patents in Russian Federation. The article highlights the problems of increasing the speed and fullness of the extraction of metals remaining after primary processing by traditional beneficiation methods, provides arguments and scientific description of the new methods of intensification of metal leaching in a disintegrator. Particular attention is paid to the effectiveness of combination of the methods of interaction with a mineral in order to increase the degree of extraction which allows to reduce operating costs. The essence of the above is the following: the scope of application of the breakthrough technology of waste-free metal extraction from deadstock poor raw materials can be improved by the use of new and prospective technologies based on the increase of process energetics. The main significance of the study lies in the experimental confirmation of the phenomenon of wastefree metal extraction into bulk concentrate by repeated activation in a disintegrator. The study’s advantage is the argument for the need of development of the new technology in order to gain economic, environmental and strategic benefits. The study is pioneering. It opens up a cluster of new problems, for example, selective extraction of metals from a collective solution, optimizing the resistance of the working body of disintegrator, utilizing master solutions, etc.